2015
DOI: 10.1016/j.jsha.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The platelet-to-lymphocyte ratio as a predictor of all-cause mortality in patients with coronary artery disease undergoing elective percutaneous coronary intervention and stent implantation

Abstract: PLR has potential predictive value in patients with SCAD, which has not been reported previously, but statistical significance disappears after adjusting for estimated glomerular filtration rate (eGFR) and hemoglobin levels as a potential confounding variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Similar to the present study, some studies show that the co-occurrence of CAE and PLR indicates a significance in univariate analysis; however, the significance disappears in multivariate and adjusted analyses [30].…”
Section: Platelet-to-lymphocyte Ratio (Plr)supporting
confidence: 89%
See 1 more Smart Citation
“…Similar to the present study, some studies show that the co-occurrence of CAE and PLR indicates a significance in univariate analysis; however, the significance disappears in multivariate and adjusted analyses [30].…”
Section: Platelet-to-lymphocyte Ratio (Plr)supporting
confidence: 89%
“…Compared to the other hematological parameters, PLR appears to be a poor marker in the prediction of cardiac surgery outcomes [30].…”
Section: Platelet-to-lymphocyte Ratio (Plr)mentioning
confidence: 97%
“…Considering the number and the heterogeneity of RCC prognostic factors and the interactions between renal cell carcinoma and immune cells, searching for widely available and reliable inflammatory biomarkers seems essential [7,9]. Up to now, numerous studies have reported that some non-specific indicators derived from complete blood count (CBC) give added prognostic value in the assessment of various diseases, including renal cell carcinoma [10][11][12][13][14][15][16]. Amongst the most promising indices that are based on absolute values of circulating inflammatory cells, platelet-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR), derived neutrophil-lymphocyte ratio (dNLR) and lymphocyte-monocyte ratio (LMR) are being particularly deeply investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Azab et al [23] reported PLR > 176 is a significant independent predictor of long term mortality after NSTEMI. Osadnik et al [24] reported PLR as a predictor of all-cause mortality in patients with coronary artery disease undergoing elective percutaneous coronary intervention and stent implantation.…”
Section: Discussionmentioning
confidence: 99%